2015
DOI: 10.1590/0100-69912015006013
|View full text |Cite
|
Sign up to set email alerts
|

Obtention of injectable platelets rich-fibrin (i-PRF) and its polymerization with bone graft: technical note

Abstract: The use of autologous platelet concentrates, represent a promising and innovator tools in the medicine and dentistry today. The goal is to accelerate hard and soft tissue healing. Among them, the platelet-rich plasma (PRP) is the main alternative for use in liquid form (injectable). These injectable form of platelet concentrates are often used in regenerative procedures and demonstrate good results. The aim of this study is to present an alternative to these platelet concentrates using the platelet-rich fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 12 publications
0
67
1
17
Order By: Relevance
“…The use of a fluid form of PRF (i-PRF) has been proposed to agglutinate the particulated bone graft material (de Mourão et al, 2015). i-PRF has been tested with different centrifugation speeds to selectively enrich leucocytes, platelets and growth factors release (Choukroun & Ghanaati, 2018).…”
Section: Sanzmentioning
confidence: 99%
“…The use of a fluid form of PRF (i-PRF) has been proposed to agglutinate the particulated bone graft material (de Mourão et al, 2015). i-PRF has been tested with different centrifugation speeds to selectively enrich leucocytes, platelets and growth factors release (Choukroun & Ghanaati, 2018).…”
Section: Sanzmentioning
confidence: 99%
“…PRF assists angiogenesis, engagement of the stem cells and migration of osteogeneous cells in the central part of the graft. 11,12 According to Toffl er M et al 10 using PRF membrane in augmentation procedures is benefi cial for better wound closure and faster recovery of the soft tissues. Other authors concluded that the use of PRF reduces postoperative pain, swelling and minimizes the infection phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing of bone graft material with pieces of PRF and its infi ltration with i-PRF leads to delivery of growth factors inside the wound, which helps the migration of osteopromotor cells and attracts circulating stem cells to the wound (fast angiogenesis). 12 Adding PRF to the bone graft reduces the required bone graft material volume and improves its manipulative qualities. The use of PRF accelerates the healing of hard and soft tissues, and the use of PRF membrane instead of another barrier membrane reduces the cost of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The original L-PRF system now exists only in one CE/FDA cleared form that is termed Intra-Spin L-PRF as stated above. A brief compilation of different types and techniques of platelet concentrate is presented in Table 1[22,26,29,32-34,41-50]. …”
Section: Evolution In Preparation Techniquesmentioning
confidence: 99%
“…Mourão et al[34] (2015) described a technique to obtain an injectable form of PRF called i-PRF. In this technique a short centrifuge for 2 min at 3300 rpm gave an orange color fluid which can be injected or mixed with bone graft to give a well agglutinated “steak” for bone grafting.…”
Section: Recent Advancesmentioning
confidence: 99%